Management of advanced renal cell carcinoma - Zhang, Xin-Wen; Jäger, Dirk; Zschäbitz, Stefanie (Oncology research and treatment, 2026)
Background: Management of advanced renal cell carcinoma (RCC) has evolved significantly in the last years. Systemic treatment of clear cell RCC, the predominant subtype, is performed with immune checkpoint inhibitors (ICIs), anti-VEGF tyrosine kinase inhibitor (TKI), HIF2 alpha inhibitors and mTOR inhibitors. Summary: The application of ICI in early disease has raised new challenges regarding subsequent therapy strategies and management of new toxicities of immunotherapy-based combination therapies. Systemic treatment for non-clear cell RCC is challenging due to the lack of robust clinical evidence for effective treatment regimens. Recent phase-2 data also indicate a benefit of ICI-combination therapies for non-clear cell RCC. For oligometastatic or oligoprogressive diseases, local therapy with cytoreductive nephrectomy, metastasectomy or stereotactic radiation can be considered. This review provides a comprehensive overview of current treatment strategies for advanced RCC, including systemic therapies for both clear cell and non-clear cell subtypes, management of treatment-associated toxicities, and the role of local therapies. Key Messages: Combination therapy for clear cell RCC is standard in first-line therapy and published data also support its use in non-clear cell carcinoma. Local therapies can be considered in selected patients. In subsequent treatment lines TKIs, mTOR inhibitors and the HIF2 alpha inhibitor belzutifan are used.